Occupational Risks in Occupational Therapy Service Learning: A Single-Site "Fear Factor" Study in South Africa - Deshini Naidoo; Pragashnie Govender; Stephanie Nicole Naidoo; Naledi Ngubane; Zamankosi Nkosi; Aziza Mulla (Hindawi-Wiley, 2020)
Background. Service-learning constitutes the main practical component of an undergraduate health profession training programme. However, limited exploration of the potential occupational risks that students face during their service-learning placement is noted in the literature. Aim. This study in South Africa explored occupational risk factors as reported by occupational therapy students whilst engaged in service-learning. Methods. In this explorative qualitative study, purposeful homogenous sampling was used to recruit third and fourth level occupational therapy students who completed a Bachelor of Occupational Therapy degree. Three focus groups were conducted with seventeen students who voluntarily participated. Audio-recorded data were transcribed and analysed thematically using deductive reasoning. Results. Several concerns over potential occupational risks were reported, namely, anxiety over contracting infectious diseases, concerns around musculoskeletal injuries due to manual handling requirements, and inappropriate behaviour of clients, which made the students feel unsafe. Concerns around the implementation of infection control measures, the lack of resources allocated to infection control at some service-learning sites, as well as the coping strategies used during service-learning were highlighted. Conclusion. Varied occupational risk factors during service-learning were reported by students. These insights into the perceived occupational risk factors can be translated into actionable strategies to improve the preparation of health science students for service-learning, including coping skills to deal with the demands of service-learning.